Subjective valuation of enrichment in restitution for wrongs - Rotherham, Craig (Informa Law, 2017)
The received wisdom is that release-fee awards, sometimes known as “Wrotham Park damages”, are available against morally blameless defendants who have committed torts of strict liability. This article argues that such defendants who have not been incontrovertibly enriched as a result of any potential benefit gained from the wrong should be entitled to rely on principles of “subjective devaluation”, rather than having their liability assessed according to the objective value of that benefit. On the other hand, in contrast to the approach taken in cases of subtractive unjust enrichment, defendants should not be protected in this way if they were careless in breaching a claimant’s rights. In addition, this article suggests that in cases of deliberate breaches where it can be shown that the defendant attached a value to the benefit in question that exceeds its market price, the defendant should be liable at that higher level. It is apparent that it is only if release fees are treated as gain-based that the interests of morally blameless defendants can be appropriately accommodated through principles such as subjective devaluation that serve to protect the autonomy of deserving defendants